3D Reconstruction of the Digestive System in Octopus vulgaris Cuvier, 1797 Embryos and Paralarvae during the First Month of Life - Fernández-Gago, Raquel; Heß, Martin; Gensler, Heidemarie; Rocha, Francisco (Frontiers in Physiology, 2017)
Octopus vulgaris aquaculture is limited due to poor biological knowledge of the paralarval stages (e.g. digestive system functionality), their nutritional requirements (e.g. adequate live diet) and standardization of rearing techniques. These factors are important in explaining the high mortality rate observed in this developmental stage under culture conditions. For a better understanding of nutrition biology of this species, we investigated the 3D microanatomy of the digestive tract of the embryo and paralarvae during the first month of life. O. vulgaris paralarvae digestive system is similar to that in the adult. The “descending branch” has a dorsal position and is formed by the buccal mass, oesophagus and crop. Ventrally, the “ascending branch” is formed by the intestine and the anus. The digestive gland, the posterior salivary glands and the inner yolk sac (in the case of the embryo and hatched paralarvae) are located between the “ascending” and “descending” branches. In the curve of the U-shaped digestive tract, a caecum and the stomach can be found. The reconstructions reveal that anatomically the digestive system is already complete when the paralarvae hatch. The reconstruction of the buccal mass at different post-hatching days has demonstrated that all the necessary structures for food intake are present. However, the radula surface in contact with the pharynx is very small on the first day of life. Although the digestive system has all the structures to feed, the digestive gland and radula take longer to reach full functionality. We have established four development periods: embryonic, early post-hatching, late post-hatching and juvenile-adult. The differentiation between these periods was done by type of feeding (endogenous or exogenous), the state of maturation and hence functionality of the digestive gland, type of growth (linear, no net or exponential), and measurement of the arm lengths with respect to the mantle length. 3D reconstruction represents a new tool to study the morphology and functionality of the cephalopod digestive system during the first days of life.